Parameters tuning optimization of second-order sliding mode control by response surface methodology - ราษฎร์ภักดี, ธนา (วารสารวิศวกรรมฟาร์มและเทคโนโลยีการควบคุมอัตโนมัติ, 2015)
In this paper, tracking performance optimization of a second-order sliding mode control (SMC), namely twisting sliding mode is considered through optimal tuning of its control parameters. Effectiveness of transient response can be achieved by considering as minimization of maximum-overshoot ( ) and settling-time ( ), which are obtained through the Response Surface Methodology (RSM). For the optimal tracking performance with the RSM, the computation process by mean of a central composite design (CCD) is performed through a quadratic equation. Finding results of a simulation confirm that the optimal tracking performance as the minimization of the and can be achieved by the optimization tuning control parameters with the RSM.